1990
DOI: 10.1002/ange.19901020122
|View full text |Cite
|
Sign up to set email alerts
|

Aufklärung der Struktur von Hormaomycin

Abstract: Anteile Benzoesiiuremethylester konnten chromatographisch [20] P. Zanello, A. Cinquantini, Transifion M e f . Chem. 10 (1985) 370. [21] Die Diamine la-c wurden durch reduktive Aminierung der entsprechenden Ketone mit Ethylendiamin/Na[BH,(CN)] in Methanol erhaltcn. ebenfalls isoliert werden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 12 publications
0
15
0
2
Order By: Relevance
“…[13] Hormaomycin is a depsipeptide antibiotic formed by Streptomyces griseoflavus W-384. [14][15][16] It also contains a pyrrole-2-carboxylic acid moiety, which is in this case attached by an amide bond to the peptide backbone of the molecule. However, in contrast to clorobiocin and coumermycin A 1 , the pyrrole The depsipeptide antibiotic hormaomycin, which is produced by Streptomyces griseoflavus W-384, contains a 5-chloropyrrole moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Hormaomycin is a depsipeptide antibiotic formed by Streptomyces griseoflavus W-384. [14][15][16] It also contains a pyrrole-2-carboxylic acid moiety, which is in this case attached by an amide bond to the peptide backbone of the molecule. However, in contrast to clorobiocin and coumermycin A 1 , the pyrrole The depsipeptide antibiotic hormaomycin, which is produced by Streptomyces griseoflavus W-384, contains a 5-chloropyrrole moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Important examples of natural nonaromatic nitro compounds are nitropropionic acid [7] and the bacterial signal metabolite hormaomycin. [8,9] Surprisingly, the biosynthesis of aromatic nitro groups is understood only to a small extent. One possible pathway involves aromatic substitution of nitro groups, as is the case for the unusual nitro alkaloid 1-nitroaknadinine (7) from Stephania sutchuenensis, which occurs simultaneously with the non-nitrated alkaloid.…”
mentioning
confidence: 99%
“…The proposed biosynthetic nitration step was mimicked in vitro with HNO 3 . [10] More recently, it was reported that a NO synthase (NOS) takes part in the nitration of the diketopiperazine thaxtomin (8), a phytotoxin produced by the plant pathogen Streptomyces turgidiscabies. [11] Additional studies revealed that tryptophan is regioselectively nitrated by a complex of Deinococcus radiodurans NOS and Trp-tRNA synthetase.…”
mentioning
confidence: 99%
“…Hormaomycin (28, Abbildung 13) ist ein anderes Hexapeptidolacton, das auch zahlreiche nichtkanonische Aminosäureeinheiten enthält, darunter zwei b-Methyl-Phe, ein Propenylprolin und ein auffälliges Nitrocyclopropylalanin. [85] Die OH-Gruppe eines Thr ist an der Bildung des Hexapeptidolacton-Makrocyclus beteiligt. Dessen Aminogruppe ist mit einem Dipeptid acyliert, der ein weiteres Nitrocyclopropyl-Ala und einen von Prolin abstammenden N-OH-2-Chlorpyrrolcarboxylrest trägt.…”
Section: Nichtproteinogene Aminosäurenunclassified